Influence of previous crops and fungicide seed treatment in the incidence and control of damping-off caused by Rhizoctonia solani in cotton seedlings under greenhouse conditions - Goulart,Augusto César Pereira (2021)
ABSTRACT The aim of this study was to verify the influence of previous crops and fungicide seed treatment in the incidence and control of damping-off caused by Rhizoctonia solani in cotton seedlings under greenhouse conditions. This experiment was carried out during two years at Embrapa Western Agriculture, in Dourados, Mato Grosso do Sul State, Brazil. In addition to cotton (treated and untreated seeds) and fallow, the following cover crops were tested as previous crops: black oats, millet, corn, forage sorghum, soybean, common beans, crotalaria (Crotalaria juncea), brachiaria (Urochloa ruziziensis) and brachiaria (Urochloa ruziziensis) + crotalaria (Crotalaria juncea). The fungicide mixture used as treatment to cotton seeds was triadimenol + pencycuron + tolylfluanid (50 + 50 + 30 g a.i./100 kg seeds). Seeds from cotton and previous crops were sown in soil contained in plastic trays and pots; the seeds were placed in individual and equidistant 3cm-deep wells. Inoculation of R. solani was obtained by homogeneously distributing the fungal inoculum onto the substrate surface (2.5g/tray and 0.34g/pot). The fungus was grown for 35 days on autoclaved black oat seeds subsequently ground to powder using a mill (1mm). Damping-off was daily evaluated from the seventh day after sowing. There was a significant effect of the interaction previous crops x fungicide treatment (P<0.05). The fungicide seed treatment was efficient in controlling seedling damping-off caused by R. solani and its effect was potentiated when grasses were the previous crops. Use of grasses such as brachiaria (Urochloa ruziziensis), black oats, millet, corn and forage sorghum as previous crops, besides fallow, significantly contributed to a smaller R. solani population in the soil, which resulted in lower rates of cotton seedling damping-off. On the other hand, using cotton continuously, as well as the legumes soybeans, beans, crotalaria (Crotalaria juncea), and brachiaria (Urochloa ruziziensis) + crotalaria (Crotalaria juncea) as previous crops to cotton, was consistently associated with higher rates of seedling damping-off, contributing to the increase or at least the maintenance of R. solani inoculum in the soil. The highest damping-off percentages were observed in plots under continuous cotton cultivation without fungicide seed treatment. The present results reinforce the need of improving damping-off control in cotton seedlings by adopting integrated management programs in areas infested with R. solani.